2015
DOI: 10.1007/978-3-319-24465-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Concept Drift: A Probabilistic Graphical Model Based Approach

Abstract: Abstract. An often used approach for detecting and adapting to concept drift when doing classification is to treat the data as i.i.d. and use changes in classification accuracy as an indication of concept drift. In this paper, we take a different perspective and propose a framework, based on probabilistic graphical models, that explicitly represents concept drift using latent variables. To ensure efficient inference and learning, we resort to a variational Bayes inference scheme. As a proof of concept, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 13 publications
(22 reference statements)
0
34
0
Order By: Relevance
“…The output generated by Code Fragment 7 is shown below. The print-out includes the distributions associated to each variable: the discrete variables have a multinomial, while the continuous ones have normal distributions given by (2). Note that, for space restriction, the generated output has been reduced.…”
Section: Static Dynamicmentioning
confidence: 99%
See 2 more Smart Citations
“…The output generated by Code Fragment 7 is shown below. The print-out includes the distributions associated to each variable: the discrete variables have a multinomial, while the continuous ones have normal distributions given by (2). Note that, for space restriction, the generated output has been reduced.…”
Section: Static Dynamicmentioning
confidence: 99%
“…In this way, AMIDST's approach to machine learning is based on the use of openbox models that can be inspected and which can incorporate prior information or knowledge about the domain, in contrast to other approaches based on blackbox models, which cannot be interpreted by the users. This is why the focus of AMIDST is not only to learn models for making predictions rather than to learn models to extract knowledge from the data [2,1]. And, as commented above, with the advantage that this toolbox is equipped with a general learning engine implementing scalable variational Bayesian inference algorithms, which allow to learn models exploiting a wide range of computational settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be a good idea to perform, for instance, a parallel cross-validation evaluation in order to determine its value. We have so far performed experiments using real datasets of different sizes and observed that the optimal batch size is generally in the order of one thousand [49,50].…”
Section: The Spliterator Interfacementioning
confidence: 99%
“…For that, we use the conditional linear Gaussian (CLG) model, which is a kind of Bayesian network with continuous and discrete nodes. Our model is based on the one proposed by Borchani et al [1,4], an approach using the CLG model and latent variables that was applied to continuous variables. Basically, we propose transforming the discrete data into continuous and then applying a similar approach with latent variables.…”
Section: Introductionmentioning
confidence: 99%